Analysis of the mechanical strength of composite materials reinforced with coconut fiber and recycled paper - I Made Kastiawan; Indah Nurpriyanti; Maula Nafi; Mastuki Mastuki; Maulana Aditya Wahyu Purnama Aji; Dimas Pribadi Nugroho (Politeknik Negeri Lhokseumawe, 2026)
Waste materials that accumulate in the environment can cause serious ecological problems. Paper waste and coconut fibres are abundant materials, and improper management of these may lead to environmental degradation. Therefore, converting waste into value-added products represents an important sustainable approach. This study explores the development of a sustainable biocomposite material composed of recycled paper waste and coconut fibers as reinforcement phases, combined with a Polyvinyl Acetate (PVA) matrix system. The composite fabrication process involved several stages. Used paper was cut into small pieces, mixed with water at a 1:1 ratio, and blended to form a damp paper pulp slurry. Coconut fibres were combed, straightened, and cut into lengths of 1-9 cm, with weight fractions of 0-40%. The paper pulp was mixed with Polyvinyl Acetate (PVA) at a fixed weight fraction of 35%, followed by the addition of coconut fibres according to the designated compositions, and then molded in accordance with ASTM standards for tensile and bending tests. This study introduces a novel fully waste-based composite system combining used paper waste and coconut fibres with Polyvinyl Acetate (PVA) as a natural matrix, demonstrating effective mechanical reinforcement without synthetic resins or cement-based binders. The highest tensile stress (12.32 MPa) was obtained at a fibre length of 9 cm and a weight fraction of 20%, while the highest bending stress (72.6 MPa) occurred at a fibre length of 1 cm and a weight fraction of 10%. The tensile strength increased by 38% compared to the fibreless composite, confirming the reinforcing effectiveness of coconut fibres. These results highlight the potential of the developed composite as a sustainable alternative material for wood-based products in non-structural applications.